The sustainable synthesis of functionalized magnetic carbon nanotube adsorbent derived from steel waste for high-efficiency sequestration of tetracycline: optimization, kinetics, isotherms and regeneration performance - Katibi, Kamil Kayode; Azis, Rabaah Syahidah; Shitu, Ibrahim Garba; Ismail, Ismayadi; Aliyu, Muhammad; Saat, Nor Kamilah; Osman, Nurul Huda; Amusa, Abiodun Abdulhameed; Iwar, Raphael Terungwa; Umar, Abba Mohammed (KeAi Communications, 2026)
Antibiotic pollution from tetracycline (TC) poses severe environmental and public health hazards. This study investigates the synthesis, characterization, and adsorptive performance of sustainable, magnetically recoverable functionalized multi-walled carbon nanotubes (FMWCNTs) adsorbent catalyzed by steel-mill waste. The adsorbent exhibits superior surface area (385 m2/g), mesoporosity (2.2 nm), and superparamagnetic behaviour (30 emu/g), enabling efficient TC adsorption and facile recovery. Optimization using response surface methodology yielded 98.7% TC removal under optimal conditions (400 mg/L FMWCNTs, 45 mg/L TC, pH 6.5, 23 min). Adsorption followed pseudo-second-order kinetics and Langmuir isotherm (maximum capacity: 21.7 mg/g at 303 K), with thermodynamic analysis indicating a spontaneous, endothermic, and entropy-driven process. The adsorbent material retained 87% efficiency after four regeneration cycles and achieved over 90% TC removal from simulated municipal effluent. Adsorption mechanisms included π-π interactions, hydrogen bonding, electrostatic attraction, and surface complexation. These findings demonstrate the promising potential of low-cost, regenerable FMWCNTs as practical adsorbents for antibiotic-polluted water.